2002
DOI: 10.1073/pnas.042678699
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus effectively mediates conditional gene modification in the brain

Abstract: The Cre͞loxP system is increasingly showing promise for investigating genes involved in neural function. Here, we demonstrate that in vivo modification of genes in the mouse brain can be accomplished in a spatial-and temporal-specific manner by targeted delivery of an adeno-associated virus (AAV) encoding a green fluorescent protein͞Cre recombinase (GFP͞Cre) fusion protein. By using a reporter mouse, in which Cre recombinase activates ␤-galactosidase expression, we demonstrate long-term recombination of neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
150
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(164 citation statements)
references
References 40 publications
14
150
0
Order By: Relevance
“…However, unlike other adenovirus vectors, the rAAV has not been shown to produce pathogenic or immune reactions, as indicated by the lack of vascular cuffing, as well as the absence of glial-, CD4-, or CD8-cell infiltration in the target site following intracranial microinjection (Kaspar et al, 2002). Moreover, it has also been shown that rAAV injection in the spinal cord of fNR1 mice does not produce neuronal loss, as measured by NeuN labeling (South et al, 2003).…”
Section: Characterization Of Cea Nr1 Knockout By Raav-gfp-cre In Fnr1mentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike other adenovirus vectors, the rAAV has not been shown to produce pathogenic or immune reactions, as indicated by the lack of vascular cuffing, as well as the absence of glial-, CD4-, or CD8-cell infiltration in the target site following intracranial microinjection (Kaspar et al, 2002). Moreover, it has also been shown that rAAV injection in the spinal cord of fNR1 mice does not produce neuronal loss, as measured by NeuN labeling (South et al, 2003).…”
Section: Characterization Of Cea Nr1 Knockout By Raav-gfp-cre In Fnr1mentioning
confidence: 99%
“…An alternative approach involves intracerebral microinjection of a recombinant adenoassociated virus (rAAV) expressing a fusion protein of Cre and a reporter, green fluorescent protein (GFP), termed "rAAV-GFP-Cre" (Kaspar et al, 2002;South et al 2003). A vector not expressing Cre (rAAV-GFP) is used as a control.…”
Section: Introductionmentioning
confidence: 99%
“…Cre recombinase can be introduced to delete the sequence between the loxP sites, producing deletion of CBP (Kang-Decker et al, 2004;Kasper et al, 2006;Xu et al, 2006). At 2 weeks before the experiments, mice were anesthetized using isoflurane and infused with adeno-associated virus expressing Cre-recombinase (AAV-Cre), either serotype AAV2/2 (made in the lab of RWG), or AAV2/1 (purchased from Penn Vector Core; University of Pennsylvania; Kaspar et al, 2002). The infusion cannula was positioned over the hippocampus (AP À2.0 mm; ML ± 1.5 mm from bregma) and lowered 0.2 mm/15 s to a depth of À1.5 mm (DV from bregma).…”
Section: Subjects and Surgical Proceduresmentioning
confidence: 99%
“…Whereas Cre has been delivered in vivo by viral gene delivery using adenovirus, lentivirus, and adeno-associated virus (36)(37)(38), the data we describe herein is the first nonviral delivery paradigm to our knowledge to deliver a biologically active Cre in vivo. Whereas viral delivery can provide high levels of stable expression, TAxI-mediated delivery of proteins offers better control over dosing and would be better tolerated in repeat dosing regimens.…”
Section: Discussionmentioning
confidence: 99%